Microplastics abundance in abiotic and biotic components along aquatic food chain in two freshwater ecosystems of Pakistan. (February 2023) - Qaiser, Namra; Sidra, Safdar; Javid, Arshad; Iqbal, Asia; Amjad, Maria; Azmat, Hamda; Arooj, Fariha; Farooq, Komal; Nimra, Afzal; Ali, Zulfiqar
Abstract: Contaminants of global concern, microplastics (MPs) have been lately reported to be found almost everywhere. Yet there is limited evidence to suggest if these tiny particles can bioaccumulate and biomagnify along the food chain. The current study was conducted to quantify MPs load in two fresh water bodies i.e. River Ravi (Pakistan) and a fish rearing pond fed with ground water to trace MPs along the food chain including biotic and abiotic components. Samples were taken from air, water, sediments, planktons, fish and avian specimen from both water bodies. Higher MPs were found in all samples taken from river Ravi ranging from 3.0 ± 1.58 MPs items in water to 15.20 ± 3.35 MP items in air as compared to 2.8 ± 1.79 MPs in water to 11.20 ± 1.89 air-borne MP items in fish rearing ponds respectively. The mean value of MP items in the GIT of all species was higher (5.05 ± 2.25) as compared to the respiratory tract (1.57 ± 1.3) suggesting ingestion as main mode of exposure. However, this mode of exposure needs to be further investigated along with other exposure routes. Presence of MPs at all trophic levels under investigation indicates some degree of bioaccumulation of these pollutants in the ecosystems. Graphical abstract: Image 1 Highlights: The primary mode of exposure of microplastics is ingestion in living beings. Microfragments were found in higher numbers in abiotic samples. Microfibers were found in higher numbers in GIT. Levels of MPs decreased along the food chain. Trophic transfer of microplastics is possible along a food chain.